The Role of Integrated Assessment in Enhancing Language Skills Development - Kuspandi, Nabila Samira; Firdaus, Masagus (CV. PUSDIKRA MITRA JAYA, 2025)
Integrated assessment is increasingly recognized as an essential component in language education, especially in English as a Foreign Language (EFL) settings. Unlike traditional assessments that isolate language skills, integrated assessment combines two or more skills in meaningful tasks that reflect authentic language use. This article investigates the role of integrated assessment in enhancing language skills development through a literature review and qualitative classroom-based study. The findings suggest that integrated assessment not only promotes communicative competence but also supports critical thinking, learner autonomy, and engagement. The paper highlights practical strategies for implementing integrated assessment and provides recommendations for educators and policymakers.